PENGEMBANGAN LABORATORIUM STATISTIKA BERBASIS ANDROID - Hanike, Yusrianti; Nurjannah, Siti (Politeknik Statistika STIS, 2023)
The importance of practicum as a forum for theoretical explanations has strong support in the knowledge transfer process, so it needs to be embodied in the learning process in a form that is easily accessible to students. The development of a statistics-based laboratory is one of the solutions to make it easier for students to access statistical software which is difficult and has a large capacity. The aim of developing an Android-based statistics laboratory is to implement statistical science and is supported by practicality and effectiveness tests for students and lecturers. The research method is carried out through five stages, namely assessment, design, development, implementation, and evaluation. The research samples were taken from two study programs (prodi) at two tertiary institutions in Ambon, namely the Statistics study program at Pattimura University and the Sharia Economics study program at the State Islamic Institute (IAIN) Ambon. The results showed that the Android-based Statistics Laboratory had a significant percentage of the feasibility, practicality and effectiveness of statistical practicum with a feasibility rating of 71%, practicality of 79% and 75% indicating the effectiveness of using the application.